An X‐ray investigation of stereoselectivity in the interactions of [Co(en)3]3+ with [Co(ox)3]3− (en is ethane‐1, 2‐diamine and ox is oxalate). Issue 4 (4th March 2022) - Gallagher, Megan K.; Baker, Jonathan; Black, Robert; Oliver, Allen G.; Lappin, A. Graham
Abstract : [Co(en)3 ][Co(ox)3 ]·5H2 O shows stereoselective hydrogen‐bonding interactions depending on the axis of interaction of [Co(en)3 ] 3+ . This has implications for chiral discriminations in solution. Abstract : The X‐ray structure of racemic tris(ethane‐1, 2‐diamine‐κ 2 N, N ′)cobalt(III) tris(oxalato‐κ 2 O 1, O 2 )cobaltate(III) pentahydrate, [Co(C2 H8 N2 )3 ][Co(C2 O4 )3 ]·5H2 O or [Co(en)3 ][Co(ox)3 ]·5H2 O, has been determined. Hydrogen‐bonding interactions along the C 3 ‐axis of the [Co(en)3 ] 3+ cation with the [Co(ox)3 ] 3− anion are heterochiral, while those perpendicular to this axis are homochiral. Implications for the interpretation of chiral discriminations and induction in electron‐transfer reactions in solution are discussed.